Pd-catalyzed regioselective mono-arylation: quinazolinone as the inherent directing group for C(sp(2))-H activation - Garad, Dnyaneshwar N.; Viveki, Amol B.; Mhaske, Santosh B. (Journal of Organic Chemistry, 2017)
The Pd-catalyzed quinazolinone-directed regioselective monoarylation of aromatic rings by C-H bond activation is developed. A broad substrate scope is demonstrated for both quinazolinone as well as diary-liodonium triflates. The use of a base was found to be crucial for this transformation, unlike for the known nitrogen-directed arylations. All of the novel quinazolinones of biological interest were synthesized by using the operationally simple Pd(II)-catalyzed arylation reaction.
Keywords: Aromatic rings; catalysis; Chemical activation; Chemical reactions; Palladium compounds; Regioselectivity

Ruthenium-catalyzed regioselective alkenylation/tandem hydroamidative cyclization of unmasked quinazolinones using terminal alkynes - Viveki, Amol B.; Mhaske, Santosh B. (Journal of Organic Chemistry, 2018)
Ruthenium-catalyzed amide directed C-sp2-H activation of the quinazolinone scaffold has been demonstrated, leading to the selective mono- or dialkenylation in moderate to good yields to achieve medicinally important stilbene containing quinazolinones. The terminal allcyne is utilized as a coupling partner, which resulted in the selective trans-alkene formation. Electron-deficient phenylacetylenes facilitate alkenylation followed by tandem hydroamidation of the newly generated trans double bond to provide novel quinazolinone alkaloids related to the Luotonine class of natural products.

Para-selective copper-catalyzed C(sp(2))-H amidation/dimerization of anilides via a radical pathway - Viveki, Amol B.; Garad, Dnyaneshwar N.; Gonnade, Rajesh G.; Mhaske, Santosh B. (Chemical Communications, 2020)
Copper-catalyzed amidation/dimerization of anilides via regioselective C(sp(2))-H functionalization is achieved. The para-selective amidation is accomplished on the anilide aromatic ring via a radical pathway leading to C-N bond formation in the presence of ammonium persulfate as a radical source/oxidant for the copper catalyst. The developed protocol tolerates a wide range of anilide substrates. The regioselectivity is confirmed by single-crystal X-ray studies.

Annulation of enals with carbamoylpropiolates via NHC-catalyzed enolate pathway: access to functionalized maleimides/iso-maleimides and synthesis of aspergillus FH-X-213 - Viveki, Amol B.; Pol, Mahesh D.; Halder, Priyanka; Sonavane, Sameer R.; Mhaske, Santosh B. (Journal of Organic Chemistry, 2021)
Herein we report the N-heterocyclic carbene (NHC)-catalyzed [3 + 2] annulation of alpha,beta-unsaturated aldehydes with carbamoylpropiolates via an unusual enolate pathway leading to the construction of highly functionalized maleimides or isomaleimides. The electronic effect imposed by the alkyl/aryl group present on the amide nitrogen of carbamoylpropiolates plays a crucial role in the selective formation of these important five-membered heterocyclic building blocks. The developed protocol is mild and tolerates a wide range of substituents on both substrates. The application of this protocol in the synthesis of the antibacterial natural product Aspergillus FH-X-213 has also been demonstrated.